Comparative Study of Bactericidal Activity of Blood Serum against Escherichia Coli in Urban and Slum Population of Bangladesh - Karim Fahareen Binta Mosharraf, Mehnaz; Ahsan, Shabnam; ., . (International Journal of Engineering and Technology, 2018)
Bangladesh is a high densely populated country. Due to the lack of socio economic development it is exposed to lots of water-borne diseases. Of them, Escherichia coli or E.coli is a Gram-negative, facultative anaerobic, rod-shaped, coliform bacterium of the genus Escherichia that is commonly found in the lower intestine of humans and can cause Bloody Diarrhea. This study will help us to analyze whether the exposure of E.coli, may accompaniment the activity of human blood serum, which is affected by the socio economic difference in the privileged and under privileged population of Bangladesh. The lifestyle of these two groups are quite different. They do not have similar facilities (in terms of balanced nutritional availability and standard vaccination plan) and hygiene conditions. The population living in slum areas, often privations these and hence expected to be more exposed to the pathogen E.coli. The design of this experiment is based on regression analysis by varying serum activity against E.coli at 0 minute (initial time) and at 180 minutes, observed in benefited and slum population of urban areas, which has been checked for adequacy and significance via Excel. It will improve our thought about the exposure of various population groups to this bacteria and their response against it. However the under privileged group showed more effective complement mediated killing in comparison to privileged population.Â Â